Navigating Nexus: Cross-Mapping Sustainable Development Goals and Competitiveness for a Resilient Future - Qazi, Abroon (2025)
This study investigates two established sustainability metrics—the Sustainable Development Goal Index (SDGI) and the Global Sustainable Competitiveness Index (GSCI)—to explore dependencies between their associated drivers using Bayesian Belief Networks (BBNs). The analysis considers sustainability performance data for 163 countries in 2023, using data from SolAbility’s Sustainable Competitiveness Report and the Sustainable Development Report. The predictive accuracy of the models used in this study is 85.1% for the SDGI and 70.6% for the GSCI for the two extreme states. Key findings underscore the strong interdependence between social and economic SDG dimensions and GSCI, whereas the environmental dimension appears relatively isolated in its contribution toward overall competitiveness. The study identifies key sustainable competitiveness pillars such as governance, social capital, and intellectual capital, highlighting their significant impact on SDGI outcomes. The results reveal that high competitiveness does not uniformly translate to high performance across all sustainability dimensions—with notable disparities in terms of environmental performance. Similarly, strong SDGI performance does not guarantee excellence in sustainable competitiveness. Scenario analysis reveals that high performance in ‘governance’, ‘social capital’, and ‘intellectual capital’ yields a 100% probability of achieving high SDGI performance. Moreover, high performance across the economic, social and environmental SDG dimensions ensures a 52% probability of achieving high sustainable competitiveness. BBNs reveal complex interrelationships among SDG dimensions and the various pillars of sustainable competitiveness, offering a more integrated and holistic approach compared to traditional methods. The proposed approach allows for the identification of critical drivers and offers a framework for scenario analysis, which can inform targeted policymaking and business strategies aimed at enhancing sustainability performance.